If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying G(x) = 2f(x + -1) Multiply G * x xG = 2f(x + -1) Reorder the terms: xG = 2f(-1 + x) xG = (-1 * 2f + x * 2f) xG = (-2f + 2fx) Solving xG = -2f + 2fx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2fx' to each side of the equation. -2fx + xG = -2f + 2fx + -2fx Combine like terms: 2fx + -2fx = 0 -2fx + xG = -2f + 0 -2fx + xG = -2f Reorder the terms: 2f + -2fx + xG = -2f + 2f Combine like terms: -2f + 2f = 0 2f + -2fx + xG = 0 The solution to this equation could not be determined.
| -6n+4=15 | | g+e=r | | 391=(x+6)-x | | 8-4z=-14-4z | | 5(32)-32=0 | | x-5(4x)+7=35 | | 34=-4r | | 2(x+8)=3(-6) | | I=2000(0.204) | | -5+5x=5x-5 | | X^2+4=134 | | -4=5n-1 | | 14r^3+21r^2-4r-6=0 | | 7q+23=15q-33 | | -x^3-2x^2-3= | | 4x-6+x+3=90 | | I=2000(0.051)(4) | | 6(6-x)-3x=24-6x | | 21m=49 | | Y=123455666+(4+2) | | a=5a-52 | | X^2+y=8 | | 30m=25 | | 58a^2-9a-30= | | 2x+x+7+y=89 | | 31=n+13 | | 14x^2=-12x | | 5x+(-3x)-32=0 | | r=4(m-3h) | | 1-3n+n=1+8n | | 7x(x^2+5)= | | (3+-4x)(4+-3x)= |